Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1198/016214504000000557
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Estimation of the Spectral Density of a Time Series

Abstract: This article describes a Bayesian approach to estimating the spectral density of a stationary time series. A nonparametric prior on the spectral density is described through Bernstein polynomials. Because the actual likelihood is very complicated, a pseudoposterior distribution is obtained by updating the prior using the Whittle likelihood. A Markov chain Monte Carlo algorithm for sampling from this posterior distribution is described that is used for computing the posterior mean, variance, and other statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
182
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(183 citation statements)
references
References 31 publications
1
182
0
Order By: Relevance
“…Thus Schwartz's theorem is the right tool for studying consistency in semiparametric models. Extensions of Schwartz's consistency theorem to independent, nonidentically distributed observations have been obtained by Amewou-Atisso et al (2003) and Choudhuri et al (2004a). The former does not use sieves and hence is useful only when weak topology is put on the infinite-dimensional part of the parameter.…”
Section: Theorem 1 Let θ = M(z + ) With the Total Variation Distancementioning
confidence: 94%
See 3 more Smart Citations
“…Thus Schwartz's theorem is the right tool for studying consistency in semiparametric models. Extensions of Schwartz's consistency theorem to independent, nonidentically distributed observations have been obtained by Amewou-Atisso et al (2003) and Choudhuri et al (2004a). The former does not use sieves and hence is useful only when weak topology is put on the infinite-dimensional part of the parameter.…”
Section: Theorem 1 Let θ = M(z + ) With the Total Variation Distancementioning
confidence: 94%
“…Using the contiguity result of Choudhuri et al (2004c), the following result was shown by Choudhuri et al (2004a) under the above assumptions.…”
Section: Bernstein Polynomial Priormentioning
confidence: 99%
See 2 more Smart Citations
“…The study of asymptotic properties of Bayesian nonparametric methods methods was initiated by the seminal papers of [Schwartz, 1965,Barron, 1988 then increased significantly after the works of [Barron et al, 1999, Ghosal et al, 2000a. Since then posterior concentration has been extensively studied in various types of models including nonparametric regression [Ghosal and van der Vaart, 2007], Markov models [Tang and Ghosal, 2007], Gaussian time series [Choudhuri et al, 2004. In this paper, we present some recent advances in the study of frequentist properties of Bayesian nonparametric inference.…”
Section: Overviewmentioning
confidence: 99%